Análisis palinofacial de la aloformación Playa del Zorro (Mioceno tardío/Plioceno), Valle del Cajón, Catamarca, Argentina - Horn, Maricel Yanina (2016)
This paper presents the palynofacies analysis results from La Cascadita locality of Playa del Zorro Alloformation (Late Miocene-Pliocene), being the first palynological study of the Neogene outcrops of the Cajon Valley, northwestern Argentina. Eleven palynological and organic matter samples were analyzed, only three of them containing palynomorphs (spores of Glomus sp. and Lycoperdon sp., Chlorophyta algae colonies, spores Zygnemataceae and few angiosperm pollen grains). Four types of organic matter were identified: phytoclasts (translucent and opaque), palynomorphs, amorphous organic matter and zooclasts. Given the overall frequency of these types and relative frequencies of the particles that constitute them, two palynofacies can be distinguished. The Palynofacies Type I is characterized by the relatively high frequency semi-opaque and equidimensional opaque phytoclasts, reduced organic amorphous matter and low representativeness of palynomorphs; suggesting oxidizing environments, poor transport and high-energy environment. The Palynofacies Type II is characterized by high relative frequency of palynomorphs and amorphous organic, and have the lower values of phytoclasts, which suggests an environment with more reducing conditions than those of the Palynofacies I, temporarily anoxic and shallow. The climate regime would have been warm, semi-arid with a marked dry seasonality.